A new nonlinear DNA model - Martín-Landrove, Miguel; González, Jorge A. (Ciencia, 1970)
The torsional dynamics of DNA can be described by nonlinear models, predicting soliton open states related to replication and transcription processes. In particular, the Yakushevich model yields soliton solutions with appropriate topological properties to describe those processes. In the present work, we developed a model that combines the dynamical aspects of both Yakushevich and Yomosa models, treating the stacking interaction between adjacent bases in a nonlinear way. By doing so, both transversal and longitudinal interactions are treated on the same foot. Stable soliton solutions, energies and its dynamics were obtained.